The motorway achievement. Volume 3, - McCoubrey, William James (Thomas Telford, 2009)
This volume presents detailed and comprehensive accounts of the construction of the motorway network, associated structures and who was involved. Each of the ten chapters focuses on a specific region of the UK, providing a background history of the area and its roads.